Chromosome-level genome assembly of Aldrichina grahami, a forensically important blowfly. Issue 3 (19th March 2020) - Meng, Fanming; Liu, Zhuoying; Han, Han; Finkelbergs, Dmitrijs; Jiang, Yangshuai; Zhu, Mingfei; Wang, Yang; Sun, Zongyi; Chen, Chao; Guo, Yadong; Cai, Jifeng
Abstract: Background: Blowflies (Diptera: Calliphoridae) are the most commonly found entomological evidence in forensic investigations. Distinguished from other blowflies, Aldrichina grahami has some unique biological characteristics and is a species of forensic importance. Its development rate, pattern, and life cycle can provide valuable information for the estimation of the minimum postmortem interval. Findings: Herein we provide a chromosome-level genome assembly of A. grahami that was generated by Pacific BioSciences sequencing platform and chromosome conformation capture (Hi-C) technology. A total of 50.15 Gb clean reads of the A. grahami genome were generated. FALCON and Wtdbg were used to construct the genome of A. grahami, resulting in an assembly of 600 Mb and 1, 604 contigs with an N50 size of 1.93 Mb. We predicted 12, 823 protein-coding genes, 99.8% of which was functionally annotated on the basis of the de novo genome (SRA: PRJNA513084) and transcriptome (SRA: SRX5207346) of A. grahami . According to the co-analysis with 11 other insect species, clustering and phylogenetic reconstruction of gene families were performed. Using Hi-C sequencing, a chromosome-level assembly of 6 chromosomes was generated with scaffold N50 of 104.7 Mb. Of these scaffolds, 96.4% were anchored to the total A. grahami genome contig bases. Conclusions: The present study provides a robust genome reference for A. grahami that supplements vital genetic information for nonhuman forensic genomics and facilitates the future research of A. grahami and other necrophagous blowfly species used in forensic medicine.